Assessment of the Possibility of Vertical Transmission of COVID-19: A Systematic Review and Meta-analysis Protocol - Sareh Dashti; Tahereh Fathi Najafi; Hamid Reza Tohidinik; Narjes Bahri (Gonabad University of Medical Sciences, 2021)
Background: The Coronavirus disease 2019 (COVID-19) outbreak has put a great burden on global health and healthcare systems. There is controversy regarding the possibility of vertical transmission of COVID-19. This proposed systematic review will be done to assess the possibility of vertical transmission of COVID-19 based on currently published literature. Methods: In this study, all published observational studies, including cross-sectional, cohort, and case-control studies, as well as case reports and case series, in peer-reviewed journals in any language until the end of July 2020 will be assessed. Editorials, commentaries, and letters to editors will be excluded from the review. Searching will be conducted using international bibliographic databases, including PubMed, Embase, and Web of Science based on Preferred Reporting Items for Systematic reviews and Meta-Analysis (PRISMA) checklist. The search strategy will be improved and finalized based on the results of the primary search. Data extraction of the included articles will be performed by two researchers using the Zotero and review manager (revMan) software. The heterogeneity of the articles will be assessed using DerSimonian & Laird Q test and I2 statistic. The pooled estimated prevalence of vertical transmission of COVID-19 will be performed using the Metaprop command. Publication bias will be assessed using Begg's rank correlation and the Egger weighted regression methods Results: Based on the reviewers comments the results section was deleted because this manuscript was a systematic review protocol. Conclusion: The findings of this study will help practitioners and health care providers in decision-making for the care and management of COVID-19-infected pregnant women.